Healthy tourism initiatives at destinations: opportunities and challenges - I Made Ady Wirawan (Universitas Udayana, 2018)
Last but not least is the interaction between the various professions in the health sector especially doctors, nurses, and public health experts. This inter-professional collaboration coupled with cross-sectoral collaboration with the tourism sectors, including the government and the tourism industry, will play a major role in the realization of tourism health efforts in accordance with the concepts described in this article. If this can work well, a vision for healthy tourism can be a reality.